Analisis Strategi Kepemimpinan dalam Meningkatkan Kinerja Pegawai di Dinas Perdagangan dan Ketenagakerjaan Kota Gunungsitoli (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the leadership strategies implemented at the Gunungsitoli City Trade and Manpower Office to improve employee performance and identify key challenges in this process. The method used is a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of structural officials who play a role in implementing leadership strategies and managing employee performance. The results of the study indicate that the leadership strategy in the agency has had a positive influence on improving employee performance through providing work direction, supporting competencies, creating a conducive work environment, and open communication. However, the implementation of this strategy still faces several obstacles, including a suboptimal reward system, limited career development, and a lack of documentation of work standards. Furthermore, leadership effectiveness also depends on the leader's ability to respond to organizational dynamics adaptively and communicatively. Therefore, this study concludes that strategic and adaptive leadership is essential for creating quality and sustainable employee performance. This research is expected to provide theoretical and practical contributions to the formulation of leadership strategies in the public sector, particularly in local government environments.